School Organizational Culture in Improving to the Teachers' Performance - Paulus Mikku Ate (Universitas Negeri Malang, 2015)
Budaya Organisasi Sekolah dalam Meningkatkan Kinerja Guru Abstract: The purpose of this research to know the process of the formation of organizational culture in improving teacher performance. This study used qualitative methods with multicase study design. Location of the study in two private schools in Southwest Sumba, East Nusa Tenggara, data collection is done by interview, observation and documentation. Analysis of the data using an interactive model Milles and Huberman, and crosscase inductive analysis Conceptually The results are influenced school organizational culture core values embraced, lived, and implanted the founders, replacement, and leader; organizational culture affects the teacher's performance; and efforts to perpetuate the culture of the organization through the determination of the leaders by the foundation, the use of uniforms, discipline, and implement celebrations. Key Words: organizational culture, teacher performance   Abstrak: Tujuan penelitian ini untuk mengetahui proses terbentuknya budaya organisasi dalam meningkatkan kinerja guru. Penelitian ini menggunakan metode kualitatif dengan rancangan studi multi kasus. Lokasi penelitian di dua sekolah swasta di Kabupaten Sumba Barat Daya, Nusa Tenggara Timur, pengumpulan data dilakukan dengan wawancara, pengamatan dan dokumentasi. Analisis data menggunakan model interaktif Milles dan Huberman, dan analisis lintas kasus secara induktif konseptual. Hasil penelitian adalah budaya organisasi sekolah dipengaruhi nilai-nilai pokok yang dianut, dihidupi, dan ditanamkan para pendiri, pengganti, dan pemimpin; budaya organisasi mempengaruhi kinerja guru; dan upaya melanggengkan budaya organisasi melalui penentuan pemimpin oleh yayasan, penggunaan seragam, penegakan disiplin, dan melaksanakan perayaan.  Kata kunci: budaya organisasi, kinerja guru